Implementasi Hukum Perbankan Syariah dalam Sistem Perbankan di Indonesia - Joni Sandri Ritonga; Fradilla Dewi Anggraini; Kennadem Kurnia Putri; Lola Fridayani; Novita Safitri; Rizka Ananta Putri; Sakinah Halim Manurung; Syahna Ariesta; Virliza Muflih; Z.Ardyansyah (Jurnal Visi Manajemen, 2024)
The development of Islamic banks is considered to have a positive impact on improving the economy of the community, which creates the impression that the revival of the Islamic economy is part of the revival of the Muslim economy. This is marked by the enthusiasm of the community in welcoming the presence of Islamic banks. This study uses a normative juridical method that focuses on the analysis of the application of positive legal norms or legal rules that apply in Indonesia, as well as the approach taken through relevant laws and regulations, with a conceptual approach. The implementation of Islamic banking law in the Indonesian banking system is regulated through the Banking Law, which shows the existence of Islamic banking in Indonesia. However, in reality, the application of sharia principles in the banking sector is still mixed with conventional banking, so that Islamic banks are often considered only as a title, because they have not been able to operate independently and fully implement the sharia principles that they should.